Effect of communication skills training on radiation therapy student's confidence and interactions during their first clinical placement. Issue 1 (February 2021) - Kelly, T.; Surjan, Y.; Rinks, M.; Warren-Forward, H.
Abstract: Introduction: The University of Newcastle, Radiation Therapy degree (RT) includes a clinical reasoning module that provides students with the opportunity to learn and practice communication skills before their first clinical placement. This study investigates students' perceptions of how well the module prepared them for placement and explores students' perceptions of their communication experiences during placement. Methods: A single survey was administered to students four months following placement (six months after delivery of module), and included a request for perceptions pre-module, post-module and pre and post placement via an online survey comprising 46 closed, Likert scale and open-response questions. Assessment of changes in student confidence, the value of preparation for placement and perceptions concerning interpersonal skills with patients and radiation therapists (RTTs) were examined. Survey data was analysed quantitatively (counts, Fisher's exact) assessing statistical differences in confidence and Weighted Sum Average (WSA) of Likert scales. Qualitative findings were supported by written comments. Results: Participants reported increasing confidence levels between pre-module (WSA - 1.13), and post-module (2.88), which was statistically significant (p = 0.039) and between pre-placement (2.0) and after placement (3.38), in their ability to communicate with patients. Similar changes in confidence were noted with interactions with RTTs (WSA scores 1.0, 2.13, 1.75, 3.25 resp). Students reported communication strategies prepared them well for patient interactions. Positive reinforcement from RTTs was acknowledged as creating immediate support of their current patient skills. Conclusion: Undertaking the clinical reasoning module successfully increased students' confidence and provided opportunities to develop appropriate communication skills for placement. Implications for practice: Increased levels of confidence and positive reinforcement from RTTs should positively impact students' knowledge and skills, and provide introspection for improvement for future placements.